Pengaruh Beban Kerja dan Disiplinan Kerja terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Mediasi - Ken Satrio Utomo; Harif Amali Rivai; Laura Syahrul (SAFE-Network, 2024)
The aim of this research is to determine the effect of workload and work discipline on employee performance with job satisfaction as a mediating variable. The research method used is a quantitative method. The data analysis technique used in this research is structural equation modeling or what is usually called Structural Equation Modeling (SEM). The results of the research are that Workload (BK) has a positive and significant effect on Employee Performance (KK) of the PLN West Sumatra Main Distribution Unit. This shows that the greater the workload, the higher the employee's performance. Workload (BK) has a positive and significant effect on Job Satisfaction (KK) of PLN West Sumatra Main Distribution Unit employees. This shows that the greater the workload, the higher the job satisfaction. Work Discipline (DK) has a positive and significant effect on Employee Performance (KK) of the PLN West Sumatra Main Distribution Unit. This shows that the greater the practice of work discipline, the higher the employee's performance. Work Discipline (DK) has a positive and significant effect on Job Satisfaction (KE) of PLN West Sumatra Main Distribution Unit employees. This shows that the greater the practice of work discipline, the higher the job satisfaction. Job Satisfaction (KK) has a positive and significant effect on Employee Performance (KK) of the PLN West Sumatra Main Distribution Unit. This shows that the greater the job satisfaction, the higher the employee's performance. Job Satisfaction (KK) mediates the relationship between Workload (BK) and Employee Performance (KK) and has a negative and significant influence. This shows that the greater the workload, which is mediated by job satisfaction, the lower employee performance will be. Job Satisfaction (KK) mediates the relationship between Work Discipline (DK) and Employee Performance (KK) because it has a positive and significant influence. This shows that the greater the work discipline mediated by job satisfaction, the greater the employee's performance.